2022
DOI: 10.1186/s12302-022-00655-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of agricultural waste biomass as raw material for the construction sector: an analysis of sustainable and circular alternatives

Abstract: Background The agricultural and construction sectors demand enormous amounts of natural resources and generate environmental impacts that negatively affect ecosystems. One of the main problems is the generation and inadequate management of waste. For this reason, under the approaches of the new sustainable and circular models, waste valorization has been prioritised as a strategy for advancing towards the sustainability of production systems. This research aims to carry out a general analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 88 publications
1
13
0
Order By: Relevance
“…The shift towards a more intentional adoption of these principles gained momentum as scientific understanding advanced and policymakers recognized the potential of sustainable agricultural practices [21]. Historical practices of communities utilizing crop residues for livestock feed or using organic waste as fertilizers provide glimpses into early circular economy practices within agriculture [12].…”
Section: Agricultural Waste and The Circular Economymentioning
confidence: 99%
See 1 more Smart Citation
“…The shift towards a more intentional adoption of these principles gained momentum as scientific understanding advanced and policymakers recognized the potential of sustainable agricultural practices [21]. Historical practices of communities utilizing crop residues for livestock feed or using organic waste as fertilizers provide glimpses into early circular economy practices within agriculture [12].…”
Section: Agricultural Waste and The Circular Economymentioning
confidence: 99%
“…By valorizing agricultural waste, farmers and agricultural industries can contribute to sustainable practices, resource efficiency, and the circular economy [11]. Various approaches and technologies are now in place to recover valuable resources from this waste, including organic matter, energy, important bioactive compounds, and nutrients, reducing its negative effects on the whole ecosystem [8,10,12]. Agricultural waste contains a high amount of important bioactive compounds, including proteins, lignin, polyphenols, fibers, and carbohydrates, which can be used as raw materials for various products, such as soil nutrients, bio-pesticides, organic matter [13], energy [14], bio-based oil [15], plastics [16], and leather, paper, and board [17], as well as other agricultural, food, and pharmaceutical goods [18].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that factors such as temperature, residence time, biomass composition, and gasification agent influence tar formation and composition [13]. Various reactor configurations, such as downdraft, updraft, and circulating fluidized bed gasifiers, have been investigated to minimize tar content and enhance gasification efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the concerning problems are seasonal availability, variable quality and composition, transportation and handling costs. Additional cementitious elements like fly ash, blast furnace slag, and silica fume are frequently utilised as (partial) cement replacement materials to lessen the environmental impact in the construction industry [8]. Although these materials are by-products of an industry that are not accessible everywhere, such as in developing nations.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%